Maternal choices and preferences for screening strategies of gestational diabetes mellitus: A exploratory study using discrete choice experiment - Xu, Tingting; Jiang, Yan; Guo, Xiuyan; Campbell, Julie A.; Ahmad, Hasnat; Xia, Qing; Lai, Xiaozhen; Yan, Di; Ma, Liangkun; Fang, Hai; Palmer, Andrew J. (Frontiers in Public Health, 2022)
This study aimed to investigate maternal preferences for gestational diabetes mellitus (GDM) screening options in China to identify an optimal GDM screening strategy. Pregnant women at 24−28 gestational weeks were recruited from Shandong province, China. A discrete choice experiment (DCE) was conducted to elicit pregnant women’s preferences for GDM screening strategy defined by five attributes: number of blood draws, out-of-pocket costs, screening waiting-time, number of hospital visits, and positive diagnosis rate. A mixed logit model was employed to quantify maternal preferences, and to estimate the relative importance of included attributes in determining pregnant women’s preferences for two routinely applied screening strategies (“one-step”: 75g oral glucose tolerance test [OGTT] and “two-step”: 50g glucose challenge-test plus 75g OGTT). Preference heterogeneity was also investigated. N=287 participants completed the DCE survey. All five predefined attributes were associated with pregnant women’s preferences. Diagnostic rate was the most influential attribute (17.5% vs 8.0%, OR: 2.89; 95%CI: 2.10−3.96). When changes of the attributes of “two-step” to “one-step” strategies, women’s uptake probability from full “two-step” to “one-step” significantly increased with 71.3% (95%CI：52.2%-90.1%), but no significant difference with the first step of “two-step”(-31.0%,95%CI:-70.2%-8.1%). Chinese pregnant women preferred the “one-step” screening strategy to the full “two-step” strategy, but were indifferent between “one-step” and the first step of "two-step" strategies. A careful consideration of maternal preferences can assist clinical practitioners and healthcare policymakers in promoting GDM screening acceptability and compliance in rural China to achieve better health outcomes for mothers and babies.